In divided unity : Haudenosaunee reclamation at Grand River - McCarthy, Theresa L. (Critical issues in indigenous studies., 2016)
"In February 2006, the Six Nations community of Ontario, occupied a construction site, reigniting the struggle to reclaim land and rights in the Grand River region. Framed by intersecting themes of knowledge production, political resurgence, and the contributions of Haudenosaunee women, the book provides a model for critical Indigenous theory that remains grounded in community-based concerns and actions"--Provided by publisher